“The most exclusive village in the world”: The Utilization of Space by the Victorian Aristocracy during the London Season - Wilkins, Kathryn (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2011)
On 18 May 1859, after a “smutty journey,” Lucy Lyttelton stepped from a Britschka carriage onto the pavement of Stratton Street, Piccadilly, in the heart of the West End of London. Accompanied by her politician father, and her elder sister Meriel, Lucy had migrated from Hagley Hall, the family’s country estate in Worcestershire. Four weeks later, Lucy travelled to St. James’s Palace with “awestruck anticipation,” to be presented to Queen Victoria; she was officially “out” in Society. For the three months that followed, Lucy was engaged in a whirl of socializing that characterised the West End during the period. She attended concerts and dinner parties dressed in expensive gowns, and danced with eligible suitors in crowded ballrooms. During the day, she rode along Rotten Row in Hyde Park in the family’s carriage, accompanied by her Aunt Catherine, the wife of Prime Minister William Gladstone. In the afternoon she gossiped with her equally aristocratic and titled friends, plotting the capture of a suitable husband at the next ball or private party.Lucy’s life in London was mirrored by thousands of other debutantes and their families, each a constituent part of the “London Season.” The social whirl that occurred in this corner of the capital during the eighteenth and nineteenth centuries had significant implications for the nature of the West End at the time. The character and meaning of individual houses and streets, and entire neighbourhoods, were altered by the activities of elite families such as Lucy’s to the extent that the London Season can be understood to have been of fundamental importance in shaping space in this corner of London.This paper analyzes in depth this relationship between space and the London Season, identifying specifically the impact elites had on the West End. In so doing, the research moves beyond previous literature regarding the Season to understand the part-time nature of space, the way in which gated communities were created, the influence of elite fashion on residential spaces, and the close relationship between space and status formed during this period. These analyses make important contributions to a critical understanding of the location of the Season in the West End, and the importance of this space to the elite in the nineteenth century.